Evaluation of the physicochemical and sensory characteristics of gluten-free cookies - Silva-Paz, Reynaldo J.; Silva-Lizárraga, Roxana R.; Jamanca-Gonzales, Nicodemo C.; Eccoña-Sota, Amparo (Frontiers in Nutrition, 2024)
The increasing prevalence of celiac disease and gluten intolerance has led to increased demand for gluten-free food products in Peru. The research objective was to develop gluten-free cookies from substitute flours, evaluating their physicochemical and sensory parameters. Eight formulations were developed using 100% broad bean, chickpea, pea, kiwicha, quinoa, lentil, corn and bean flour. One hundred consumers participated in this evaluation (59% women and 41% men). A completely randomized design (CRD) and a randomized complete block design (RCBD) were used for physicochemical analysis and acceptability, respectively. To describe the sensory characteristics of the cookies, the Cochran test and correspondence analysis (CA) were applied. From the results obtained, the lentil cookie presented the highest amount of protein and fiber, but lower fat and carbohydrate content compared to the other samples. In terms of color, the corn cookie was the lightest, with greater luminosity (L*), less redness (a*) and yellowness (b*). Regarding the sensory analysis, the CATA questions allowed us to form six groups and the samples with the greatest acceptability were the corn and chickpea cookies, which were rated as "I like them." Lentil flour crackers are a nutritionally adequate option and corn flour crackers are highly sensorially acceptable, suggesting commercial opportunities for softer and more flavorful gluten-free products. However, it is crucial to continue researching and developing innovative products to meet changing market demands and offer healthier and more attractive options to consumers.